2007
DOI: 10.1111/j.1365-3040.2007.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

The Na+ transporter AtHKT1;1 controls retrieval of Na+ from the xylem in Arabidopsis

Abstract: HKT-type transporters appear to play key roles in Na + accumulation and salt sensitivity in plants. In Arabidopsis HKT1;1 has been proposed to influx Na + into roots, recirculate Na + in the phloem and control root : shoot allocation of Na + . We tested these hypotheses using 22 Na + flux measurements and ion accumulation assays in an hkt1;1 mutant and demonstrated that AtHKT1;1 contributes to the control of both root accumulation of Na + and retrieval of Na + from the xylem, but is not involved in root influx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
375
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(403 citation statements)
references
References 31 publications
20
375
1
1
Order By: Relevance
“…A similar mineral distribution mechanism has been reported for the xylem parenchyma cell-localized HKT1 (high-affinity K + transporter 1) and SKC1 (Shoot K + content 1) sodium transporters (Maser et al, 2002;Gong et al, 2004;Ren et al, 2005;Sunarpi et al, 2005). Disruption of these Na + transporters results in overaccumulation of Na + in xylem sap and shoots (Maser et al, 2002;Gong et al, 2004;Ren et al, 2005;Sunarpi et al, 2005;Horie et al, 2006;Davenport et al, 2007;Moller et al, 2009). Here, we observed that in the mutant nrt1.8-1, a greater proportion of nitrate accumulated in shoots under cadmium stress ( Figure 8B).…”
Section: Nrt18 Is An Essential Component Regulating Nitrate Distribusupporting
confidence: 54%
See 1 more Smart Citation
“…A similar mineral distribution mechanism has been reported for the xylem parenchyma cell-localized HKT1 (high-affinity K + transporter 1) and SKC1 (Shoot K + content 1) sodium transporters (Maser et al, 2002;Gong et al, 2004;Ren et al, 2005;Sunarpi et al, 2005). Disruption of these Na + transporters results in overaccumulation of Na + in xylem sap and shoots (Maser et al, 2002;Gong et al, 2004;Ren et al, 2005;Sunarpi et al, 2005;Horie et al, 2006;Davenport et al, 2007;Moller et al, 2009). Here, we observed that in the mutant nrt1.8-1, a greater proportion of nitrate accumulated in shoots under cadmium stress ( Figure 8B).…”
Section: Nrt18 Is An Essential Component Regulating Nitrate Distribusupporting
confidence: 54%
“…It is worth noting that NRT1.8 expression is also induced in shoots under prolonged Cd 2+ treatment ( Figures 6B and 6C), which may contribute to recycling nitrate from shoots to roots. This would partially contribute to increasing the root/shoot nitrate ratio ( Figure 8B), possibly via a similar mechanism proposed for HKT1/SKC1, in which Na + is unloaded from xylem vessels to xylem parenchyma cells, then transported into the phloem and recycled to roots (Maser et al, 2002;Gong et al, 2004;Ren et al, 2005;Sunarpi et al, 2005;Horie et al, 2006;Davenport et al, 2007).…”
Section: Nrt18 Is An Essential Component Regulating Nitrate Distribumentioning
confidence: 99%
“…Numerous studies have been conducted on the genetic and molecular mechanisms underlying salt tolerance in plants 18,19,30,31 , and have included genomic analyses of the extremophiles Thellungiella parvula 16 and T. salsuginea 43 . However, our current understanding of these aspects of salt tolerance remains limited, especially for woody plants 22,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the amount of K + and Na + in leaves is determined by several distinct processes: Na + /K + uptake from the soil, longdistance transport to the shoot via the xylem, and redistribution through the phloem. The function of xylem-localized HKT1 in limiting Na + translocation to the shoot has been established (Mä ser et al, 2002;Sunarpi et al, 2005;Rus et al, 2006;Davenport et al, 2007). In hkt1 mutants, xylem Na + concentration is higher than in the wild type (Sunarpi et al, 2005).…”
Section: Phloem and Na + /K + Homeostasismentioning
confidence: 99%